Optimal planning and design of hybrid renewable energy system for rural healthcare facilities / Olatomiwa Lanre Joseph - Olatomiwa Lanre , Joseph (2016)
This thesis focused on the feasibility of off-grid hybrid renewable energy in delivering basic healthcare services in rural areas without electricity access. Renewable energy resource (RES) such as solar and wind energy is considered abundant in many rural places, it is also environmental friendly, hence suitable for providing electricity in rural healthcare facilities where there is no electricity access. These energy resources have received greater attention in recent years due to their cost effectiveness in operation. Optimum planning and design of hybrid renewable power system based on location selection, component types, system configuration as well as sizing to meet the load requirements of rural healthcare facility has been considered in this study. In this case, long-term meteorological data from six selected locations across the six climatic zones of Nigeria (Sokoto, Maiduguri, Jos, Iseyin, Enugu and Port-Harcourt) were first examined to determine the feasibility of utilizing the energy resources (solar and wind) to power a typical rural healthcare facilities at respective remote locations. Followed by development of prediction algorithm for solar radiation using soft-computing methodologies. Then, utilization of cost-effective optimization algorithm for optimal sizing of the energy resources and other system components with accurate mathematical models for energy management of the entire hybrid system. The final aim is the minimization the proposed hybrid system total annual cost during the project lifetime while considering the reliability of power supply to the rural clinics and pollutant emission reduction. To this aim, cost function of PV, wind, diesel generator and battery were derived by considering the rural clinics load demand, sites meteorological (solar radiation, wind speed, temperature) data and diesel price. Findings from the study showed that Sokoto and Jos exist in the high wind potential regions, while the remaining sites are only suitable for small wind applications. Values obtained for global, beam and diffuse radiation as well as clearness index, show that all the sites enjoy considerable solar energy potential suitable for varying degree of solar energy applications. The feasibility simulation carried out with Hybrid Optimization Model for Electric Renewable (HOMER) software indicates that hybrid system is the best option for all the sites considered in this study. The PV/wind/diesel/battery hybrid system configuration is considered optimum for RHC applications at Iseyin, Sokoto, Maiduguri, Jos and Enugu, while hybrid systems involving PV/diesel/battery is considered ideal for RHC at remote location in Port-Harcourt, due to the quality of renewable energy potential. Hence, it was concluded that, the abundance of wind and solar resources in the country create an ideal environment for inclusion of renewable energy systems, such as PV and wind in the design and implementation of standalone power supply systems to improve rural health delivery. The reliability of hybrid systems is found to be enhanced when solar, wind and diesel generator are used together; the size of battery storage is also reduced because there is less dependence on one method of energy production.